2019
DOI: 10.1111/mcn.12922
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention to update health workers about HIV and infant feeding

Abstract: Clinical guidelines are used to translate research findings into evidence‐based clinical practice but are frequently not comprehensively adopted by health workers (HWs). HIV and infant feeding guidelines were revised by the World Health Organization to align feeding advice for HIV‐exposed and unexposed infants, and these were adopted in South Africa in 2017. We describe an innovative, team‐based, mentoring programme developed to update HWs on these guidelines. The intervention was underpinned by strong theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous studies in SSA have found that mixed messages which are inconsistent with guidelines [ 22 24 ] were due to frequently changing guidelines [ 23 ]. Prior to 2016, HCWs attending a training intervention update on infant feeding and HIV in SA confirmed they lacked information and skills prior to training [ 88 ]. Previous gains from the PMTCT programme in SA might be reversed due to a failure to tailor infant feeding counselling to individual needs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in SSA have found that mixed messages which are inconsistent with guidelines [ 22 24 ] were due to frequently changing guidelines [ 23 ]. Prior to 2016, HCWs attending a training intervention update on infant feeding and HIV in SA confirmed they lacked information and skills prior to training [ 88 ]. Previous gains from the PMTCT programme in SA might be reversed due to a failure to tailor infant feeding counselling to individual needs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proven innovative strategies for disseminating accurate infant feeding counselling messages to all family members, could enhance infant feeding practices. The use of community-based peer supporters [ 96 ], mobile technology [ 55 , 97 ], and introducing innovative HCW training approaches [ 88 , 98 ] have all shown promising results in bridging the knowledge and skills gaps among key stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention has been described elsewhere. 25 In summary, our participatory intervention was guided by evidence that HWs’ attitudes and practices are influenced by various factors, not just exposure to training and information. 26 We used Dee Fink’s six-part taxonomy as a guiding theory.…”
Section: Methodsmentioning
confidence: 99%